MEDICARE ADVANTAGE CONTROL OF POST-ACUTE COSTS: PERSPECTIVES FROM PLANS, HOSPITALS, AND SKILLED NURSING FACILITIES. (11th November 2018) - Gadbois, E A; Tyler, D A; Shield, R R; McHugh, J P; Winblad, U; Trivedi, A; Mor, V
Abstract: Medicare Advantage plans have strong incentives to control costs. This study aimed to understand MA efforts to control PAC spending. 154 interviews were conducted with staff from 10 MA plans, 16 hospitals, and 25 SNFs in eight markets across the country. Participants discussed how MA plans attempted to reduce PAC spending by controlling SNF selection and length of stay (LOS). Plans typically controlled SNF selection by providing patients with a list of facilities in which care would be covered. To influence LOS, MA plans commonly authorized patient stays for a limited number of days. Hospital and SNF responses to this authorization-based system were frequently negative, and participants expressed concerns about potentially deleterious consequences. In their interactions with hospitals and SNFs, MA has the power to control patient flow. However, exerting too much control can have the negative consequence of delays in hospital discharge and SNF avoidance of certain plans.